DISKURSUS TEOLOGI QADARIAYAH DAN JABARIAH : TAWAKAL DALAM TINJUAN FILOSOFIS DAN SURVEY MASYARAKAT MODERN - Irwan Supriadin J; Achmad Abubakar; Aisyah Arsyad (STIT Sunan Giri Bima, 2024)
This study examines the concept of tawakkul (trust in Allah) from the perspective of Islamic theology, specifically through the views of Qadariyah and Jabariyah, as well as its application in modern society. Tawakkul is defined as a balance between maximal effort (ikhtiar) and full reliance on Allah SWT. Using a multidisciplinary approach, this research includes an analysis of Qur'anic verses such as QS Ali Imran: 159 and QS At-Talaq: 3, along with a survey on the understanding of tawakkul among modern individuals aged 17–45. The aim is to explore the understanding of tawakkul in various aspects of life, including the workplace, stress management, and social relationships. The survey results reveal that 84.2% of respondents perceive tawakkul as a combination of effort and reliance, while 52.6% believe that tawakkul can help manage stress and enhance solidarity. The study finds that while Qadariyah emphasizes human free will and Jabariyah prioritizes divine predestination, both share the same ultimate goal of glorifying Allah. Furthermore, the research suggests that a moderate approach between these two theological perspectives is more relevant in addressing modern challenges such as social anxiety and workplace dynamics. By proposing an adaptive concept of tawakkul, this study contributes to improving the mental and spiritual well-being of Muslims in contemporary times.